Antimicrobial Resistance Trends among Community-Acquired Respiratory Tract Pathogens in Greece, 2009–2012. (30th December 2013) - Maraki, Sofia; Papadakis, Ioannis S.
Abstract : The aim of the present study was to determine the antimicrobial resistance trends of respiratory tract pathogens isolated from patients with community-acquired respiratory tract infections (CARTIs) in Crete, Greece, over a 4-year period (2009–2012). A total of 588 community-acquired respiratory pathogens were isolated during the study period. Streptococcus pneumoniae was the most common organism responsible for 44.4% of CARTIs, followed by Haemophilus influenzae (44.2%) and Moraxella catarrhalis (11.4%). Among S. pneumoniae, the prevalence of isolates with intermediate- and high-level resistance to penicillin was 27.2% and 12.3%, respectively. Macrolide resistance slightly decreased from 29.4% over the period 2009-2010 to 28.8% over the period 2011-2012. Multiresistance was observed among 56 (54.4%) penicillin nonsusceptible isolates. A nonsignificant increase in resistance of H. influenzae isolates was noted for β -lactams, cotrimoxazole, and tetracycline. Among the 67 M. catarrhalis tested, 32 produced beta-lactamase and were resistant to ampicillin. Macrolide resistance decreased over the study period. All isolates were susceptible to amoxicillin + clavulanic acid, chloramphenicol, rifampicin, and the fluoroquinolones. Although a decreasing trend in the prevalence of resistance of the three most common pathogens involved in CARTIs was noted, continuous surveillance of antimicrobial susceptibility at the local and national level remains important, in order to guide appropriate empirical antimicrobial therapy.